Update on Long-Acting Anticholinergics in Children and Adolescents With Difficult and Severe Asthma - Santamaria, Francesca; Ziello, Carla; Lorello, Paola; Bouchè, Cristina; Borrelli, Melissa (Frontiers in Pediatrics, 2022)
Tiotropium bromide is the only long‐acting muscarinic antagonist (LAMA) approved for treatment of patients aged ≥ 6 years old with severe asthma who have symptoms of uncontrolled asthma. Results from several clinical trials have found that once-daily inhaled tiotropium bromide is safe and efficacious in 6 to 17 year-olds with symptomatic asthma despite treatment with inhaled corticosteroids, with or without other medications. There are still few available studies investigating the impact of tiotropium bromide treatment in preschool children with suboptimal asthma control. In this narrative review, we summarize the pharmacological effects of the LAMA tiotropium bromide, provide an overview about current asthma studies using it at different pediatric ages, and describe future research needs.